Survey on Health, Well-being and Aging. SABE Colombia 2015: Technical report (Colombia Medica, 2019)
Introduction: Colombian population is getting old in an accelerated manner, causing economic, social and health services effects. The Ministry of Health and Social Protection in the National System of Population Studies and Surveys for Health implemented the first health, well-being and aging survey- SABE-2015 Colombia- to know the living conditions of people 60 years of age or older.Objective: Describe the design of the method, statistical sampling and quality control of information from the SABE-2015 survey.Methods: A cross-sectional study, with quantitative and qualitative approaches, representative for the population in urban and rural areas aged 60 or over. Information was collected on socioeconomic variables, physical and social environment, behavior, cognition and affection, functionality, mental well-being, health conditions, and the use and access to health services.Results: 23,694 surveys were conducted, 17,189 in urban population (72.5%) and 6,505 in rural population. The percentage of effective national response was 66% in 244 municipalities. Supervision was made in 40% of the surveys and telephone re-contact in 25%. The consistency of 100% surveys was reviewed and double entry was developed in 5% of them. National estimates have a 5% margin error.Conclusion: The SABE Colombia 2015 survey is representative of the main indicators of health, well-being and aging in Colombia. The design allows regional comparisons, between large cities and urban and rural population.